GE_GERICHTE P/7378/2010 vom 6. Januar 2014 - GE Cour de justice (2014)
CONTRAINTE SEXUELLE; FIXATION DE LA PEINE; SURSIS À L'EXÉCUTION DE LA PEINE; SURSIS PARTIEL À L'EXÉCUTION DE LA PEINE | CP.189.1; CP.47; CP.43; CP.42